PEMBARUAN TAKSONOMI, SEBARAN SPESIES DAN KUNCI IDENTIFIKASI NYAMUK DEWASA TRIBE FICALBIINI (DIPTERA: CULICIDAE) DI INDONESIA - Sidiq Setyo Nugroho (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Indonesia is an archipelago that has complex biodiversity and distribution of fauna, including mosquitoes. Indonesia currently has around 456 species of mosquitoes and is the second-largest in the world. Update on the information about the species list and distribution of mosquitoes in Indonesia compiled by O'Connor and Sopa (1981) have never been conducted for nearly 40 years. The purpose of this study is to convey taxonomic updates and species distribution as well as the key to identifying mosquito in the tribe Ficalbiini in Indonesia. The Ficalbiini tribe consists of the genus Ficalbia and Mimomyia. The author has reviewed some literature about taxonomic information, species distribution, and morphological characters of tribe Ficalbiini members. The list of species and their distribution updated with literature study and mosquitoes collection from Rikhus Vektora 2015 – 2018 organized by Balitbangkes, Ministry of Health, Indonesia. The mosquitoes were identified on the spot and confirmed in the laboratory. Identification results also have undergone an appeal with external parties. Indonesia currently has 11 species in the tribe Ficalbiini, namely Ficalbia ludlowae, Fi. minima, Mimomyia elegans, Mi. luzonensis, Mi. fusca, Mi. mogii, Mi. aurea, Mi. chamberlaini, Mi. flavens, Mi. hybrida, and Mi. modesta. Mimomyia mogii and Mi. aurea are two additional species to the species list compiled by O'Connor and Sopa (1981). The species of the tribe Ficalbiini spread throughout Indonesia, except in the Maluku islands. The identification key for species in the tribe Ficalbiini in Indonesia has never been available before. Thus, species identification key for female mosquitoes in the tribe Ficalbiini included in this paper as well.